The 1951 eruption of Mount Lamington, Papua New Guinea: Devastating directed blast triggered by small-scale edifice failure - Belousov Alexander; Belousova Marina; Hoblitt Richard; Patia Herman (My University, 2020)
The catastrophic explosion of Mount Lamington volcano, Papua New Guinea on January 21, 1951 produced a devastating pyroclastic density current (PDC) that knocked down dense tropical rainforest over an area of 230 km2 and killed approximately 3000 people. We present results of a field reinvestigation of the 1951 PDC deposit combined with an analysis of the available photographs and eyewitness accounts of the eruption first published in the fundamental work of G. A. M. Taylor (1958). We have concluded that the six-days-long pre-climactic activity before the 1951 eruption (which included felt local seismicity, frequent ash-laden explosions of vulcanian type, bulging of the volcano slope accompanied with landslides) was associated with shallow-level intrusion of a highly viscous magma body (cryptodome/dome) of andesitic composition with a volume of approximately 0.01 km3 . This intrusion destabilized Mount Lamington's prehistoric intra-crater lava dome. On January 21 the destabilized dome gravitationally collapsed and produced a relatively small-volume debris avalanche, the deposit of which was not recognized during Taylor's original investigation. The debris avalanche had a volume of approximately 0.02–0.04 km3 , travelled a distance (L) of 8.5 km and had the ratio of vertical drop (H) to runout (L) of 0.14. The edifice collapse decompressed the intruding cryptodome and triggered its explosive fragmentation.
Keywords: Mount Lamington; Papua New Guinea